Integrating neuroscience and immunology core concepts to develop a neuroimmunology curriculum - Shah, Aparna P.; Leininger, Elizabeth C.; Pandey, Sumali (Frontiers in Education, 2025)
Training students in interdisciplinary thinking is critical for the future of scientific discovery and problem-solving more generally. Therefore, students must have early opportunities to grapple with knowns and unknowns at the frontiers of interdisciplinary inquiry. Neuroimmunology challenges students to think at the intersection of two rapidly evolving fields, neuroscience and immunology. As these disciplines focus on complex systems, their intersection represents a unique opportunity for students to witness the nature and process of interdisciplinary collaboration and synthesis. However, the fast pace of research and specialized knowledge in both disciplines present challenges for instructors interested in teaching the subject to undergraduate students. In this article, we share and describe a curriculum developed using a backward-design approach to analyze core concepts in both neuroscience and immunology, which were articulated by disciplinary experts in collaboration with their respective education communities. We determine overlaps between these conceptual frameworks, identify key prerequisite knowledge, and suggest example activities to introduce neuroimmunology to undergraduate students. This curriculum may be used for an entire course, or modified into shorter units that instructors can use within diverse educational contexts. We hope that this effort will encourage instructors to adopt neuroimmunology into their curricula, provide a roadmap to forge other such interdisciplinary educational collaborations, and prepare students to develop creative solutions to current and future societal problems.